Safety assessment of biguanide antiseptics application in irrigation protocol in endodontic treatment - Czopik, Barbara (2023)
The aim of the study was quantitative analysis of PCA formation during 2% CHX activation with US and MDI methods with HPLC-DAD method and therefore safety assessment of US and MDI agitation of CHX, as well as safety assessment of 1% ALX as an alternative to 2% CHX in endodontic treatment. 2% CHX was activated with US in PUI method and MDI method for 15s, 30s, 60 and 90s. PCA concentration was assessed with HPLC-DAD. PCA concentration was also assessed for non-activated 2% CHX after 0, 3,18 and 21 days of storage. Solutions of ALX were mixed with the equivalent volume of 2% and 5.25% (w/v) NaOCl. Samples were subjected to the UHPLC-MS analysis. PCA was detected in all samples of 2% CHX in all methods of activation. The concentration of PCA was dependent on time of activation in US group (p<0.05). PCA was detected in shelf-stored 2% CHX and concentration was related to time of storage. The mixture of ALX and NaOCl resulted in a yellowish precipitate formation, the amount of which depended on NaOCl concentration. Interaction of ALX and NaOCl resulted in the production of aliphatic amines. For the first time, we identified the possible products of the interaction. Activation of 2% CHX with PUI and MDI methods does not carry higher risk of toxicity in vitro in comparison to non activated 2% CHX, as the amounts of PCA released during PUI and MDI agitation are comparable to the amoun
Keywords: root canal treatment; endodontic treatment; chlorhexidine; PCA; sodium hypochlorite